THE MODERN IDEA OF UKRAINE IN THE SOCIO-CULTURAL AND HISTORICAL REPRESENTATIONS NEOFORMATSIONNYCH - Гнатюк, Я. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article from a historical perspective in considered the modern idea of Ukraine. This idea is explored in the boundaries of socio-cultural and neoformatsionnogo approaches to understanding the history of Ukraine, the historical horizon is fixed and analyzed the implementation strategy of the modern idea of Ukraine.